Transformasi Desain Grafis Di Era AI : Pendampingan/Pelatihan Penggunaan Canva Untuk Desain Kreatif - Elin Nurcahyani; Nouzal Dwi Nindias Adam; Athallah Naufal Suwarno; Muhammad Faqih; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of Artificial Intelligence (AI) has transformed the paradigm of graphic design from manual processes to more automated and inclusive approaches. The main problem faced by students at SMK N 1 Purwokerto is the limited technical skills in creating visually appealing content for digital promotion. This community service activity aims to enhance design skills through training on the Canva platform, which is now integrated with AI features. The method used is a participatory workshop consisting of material presentation, hands-on practice, and evaluation of participants’ design outputs. The results of the activity indicate a significant improvement in participants’ understanding of design principles and their ability to utilize Canva’s AI features, such as Magic Design and Text to Image. This transformation enables participants to produce professional design works quickly and efficiently.